Penentuan Sebab Kematian Pada Kasus Gantung Diri Berdasarkan Pemeriksaan Luar Jenazah - NABIL; JULI PURWANINGRUM (HANG TUAH MEDICAL JOURNAL, 2023)
In cases of hanging, it will cause asphyxia in the victim, causing death. Cases of suicide can occur in patients who are unable to solve their problems. As many as 40% of people with depression have the idea to commit suicide with symptoms of sadness and the prevalence of suicide in Indonesia reaches 3.7 per 100,000 population. In the report on the case of hanging himself, investigators sent the body to the Corps Retrieval Unit of RSUD dr. R. Koesma Tuban on Monday 03 January 2022 at 16.20 WIB. and the doctor has carried out an external examination of the body based on a letter requesting post mortem et repertum investigators from the Tuban city police on January 4, 2022 at 09.40 WIB And the investigator only ordered to carry out a post mortem examination so as a doctor the order must be carried out even though it is more appropriate if it is accompanied by a post- mortem examination because the order was contained in the regulations per law in Indonesia, namely in article 133 of the Criminal Procedure Code. The results of an external examination of the body found lips, cyanotic nails, mucous membranes of the right and left eyes, there were bleeding spots and there were grooves in the neck area so that the conclusion was obtained that the victim had suffocated due to lack of oxygen